2013
DOI: 10.1902/jop.2013.120739
|View full text |Cite
|
Sign up to set email alerts
|

Increased Nucleic Acid Receptor Expression in Chronic Periodontitis

Abstract: This study highlights a possible role for nucleic acid receptors in periodontal inflammation. Future investigations will determine whether cytoplasmic receptors and their ligands can be targeted to improve clinical outcomes in periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 35 publications
3
43
1
Order By: Relevance
“…Although it is beyond the scope of this article, we can speculate that P. gingivalis DNA can be engaged by other nucleic acid sensors as well. In fact, our previous clinical studies also showed increased DAI expression in chronic periodontitis lesions compared to its expression in healthy tissues (14). Future studies are warranted to delineate the extent of involvement of other microbial DNA sensors in periodontitis pathogenesis.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Although it is beyond the scope of this article, we can speculate that P. gingivalis DNA can be engaged by other nucleic acid sensors as well. In fact, our previous clinical studies also showed increased DAI expression in chronic periodontitis lesions compared to its expression in healthy tissues (14). Future studies are warranted to delineate the extent of involvement of other microbial DNA sensors in periodontitis pathogenesis.…”
Section: Discussionmentioning
confidence: 79%
“…Despite having been fairly well studied in relation to various diseases of infectious or immunological origin, the role of nucleic acid sensing by intracellular PRRs in the pathogenesis of periodontitis has received little attention. Previous clinical studies from our group and others have demonstrated increased TLR9 gene and protein expression in gingival tissues associated with chronic periodontitis (14)(15)(16). TLR9 showed the highest gene expression among all innate receptors, and the increased expression was predominantly localized in the connective tissue and basal epithelial layers (14).…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…The mRNA levels of TLR2 and TLR9, but not TLR4, were positively correlated with the number of P. gingivalisin subgingival plaque. This study suggests that P. gingivalisinfection induces TLR2 and TLR9 upregulation in patients with periodontitis [33].Moreover,statistically significant upregulation of TLR9 and TLR8 have been reported in chronic periodontitis tissues compared to healthy sites [34]. In another study, gingival tissue samples were obtained from eight chronic periodontitis and nine gingivitis (3 mild; 3 moderate; 3 severe) patients.…”
Section: How Chronic Periodontitis Affects Tlr Activities?mentioning
confidence: 65%